Same game, different worlds? General conditions, perceived stress, and associations between stress and past season injuries in elite female and male ice hockey players - Tobias Wörner; Stefan Kauppinen; Frida Eek (BMC, 2024)
Abstract Background Ice hockey is played by women and men but the arena they play in may differ substantially. Potential differences in general conditions to play the sport may be associated to perceived stress, which has shown to be related to athletic injury in other sports. Therefore, this study aimed to describe and compare general conditions for playing ice hockey, stress levels, and the association between perceived stress and injury occurrence among elite female and male players. Methods Prior to the 2022-2023 season all female and male players from the top ice hockey leagues in Sweden were invited to an online survey. Players provided information about their general conditions for playing ice hockey and reported perceived stress during the previous season on the Perceived Stress Scale (PSS-10; sum score range 0-40) and current stress on the Single Item Stress Question (SISQ; scale range 1-5). Injuries during the previous season were self-reported on a modified version of the Oslo Sports Trauma Research Center - Overuse Injury Questionnaire. Results We received responses from 360 players (170 females and 190 males). Female players more frequently reported additional occupations besides ice hockey and less medical support during games and practices than male players (p < .001). General stress levels were significantly higher among female players (mean PSS score [SD]: 17.4 [5.6] vs 14.1 [5.6], p < 0.001; SISQ median [IQR]: 3 [2-3] vs 2 [1-3], p < 0.001). There was a statistically significant but weak correlation between past season injury and perceived stress (PSS score: rho 0.29; SISQ: rho 0.24). This correlation was stronger among males than females (PSS score: 0.38 vs 0.162; SISQ: 0.29 vs 0.16, p's < 0.05). Players with substantial injuries during previous season had higher previous and current stress levels than players without injury, a difference that was largest and statistically significant only among male players. Conclusions General conditions for playing elite ice hockey are inequal for female and male athletes. Stress levels of elite ice hockey players were comparable to the general population. Experience of severe injuries during the previous season was associated to higher levels of perceived stress. This association is stronger among male players, which may be due to greater economic dependency.